MicroRNA dysregulation in ataxia telangiectasia - Cirillo, Emilia; Tarallo, Antonietta; Toriello, Elisabetta; Carissimo, Annamaria; Giardino, Giuliana; De Rosa, Antonio; Damiano, Carla; Soresina, Annarosa; Badolato, Raffaele; Dellepiane, Rosa Maria; Baselli, Lucia A.; Carrabba, Maria; et al. (Frontiers in Immunology, 2024)
Introduction: Ataxia Telangiectasia (AT) is a rare disorder characterized by neurodegeneration, combined immunodeficiency, a predisposition to malignancies and high clinical variability. Profiling of microRNAs (miRNAs) may offer insights into the underlying mechanisms of complex rare human diseases, as miRNA play a role in various biological functions including proliferation, differentiation, and DNA repair. In this study we investigate the differential expression of miRNAs in samples from AT patients with the aim of identifying miRNA patterns and to investigate how these patterns are related to the disease.We enrolled twenty AT patients (mean age 17.7+9.6 years old) and collected clinical and genetic data. We performed short non-coding RNA-seq analysis on peripheral blood mononuclear cells (PBMCs) and fibroblasts to compare the miRNA expression profile between AT patients and controls.We observed 42 differentially expressed (DE)-miRNAs in blood samples and 26 in fibroblasts samples. Among these, three were further validated in additional AT samples, confirming their dysregulation.We identified an AT-related miRNA signature in blood cells and fibroblast samples collected from a group of AT patients. We also predicted several dysregulated pathways, primarily related to cancer, immune system control or inflammatory processes. The findings suggest that miRNAs may provide insights into the pathophysiology and tumorigenesis of AT and have the potential to serve as useful biomarkers in cancer research.